Nano-Sized Iron Sulfide: Structure, Synthesis, Properties, and Biomedical Applications - Yuan, Ye; Wang, Liping; Gao, Lizeng (Frontiers in Chemistry, 2020)
Nano-sized iron sulfides have attracted intense research interest due to their variety of types, structures, physicochemical properties. In particular, nano-sized iron sulfides exhibit enzyme-like activities by mimicking natural enzymes depending iron-sulfur cluster as cofactor, extending their promising applications in biomedicine. This review will mainly summarize the synthesis properties and applications of in biomedical fields, demonstrating that nano-sized iron sulfides have great potentials in improving human health and life quality.